Genome-wide identification and expression analysis of the WRKY gene family in Sophora flavescens during tissue development and salt stress - Li, Jin; Wang, Xi; Lu, Junjie; Song, Huifang; Lei, Haiying; Niu, Tianzeng; Liu, Ake (Frontiers in Plant Science, 2024)
Sophora flavescens is a traditional Chinese medicinal herb rich in various bioactive secondary metabolites, such as alkaloid and flavonoids, and exhibits remarkable resistance to abiotic stress. The WRKY transcription factor (TF) family is one of the largest plant-specific TF families and plays a crucial role in plant growth, development, and responses to abiotic stress. However, a comprehensive genome-wide analysis of the WRKY gene family in S. flavescens has not yet been conducted. In this study, we identified 69 SfWRKY genes from the S. flavescens genome and classified them into seven distinct subfamilies based on phylogenetic analysis. Transposed duplications and dispersed duplications were found to be the primary driving forces behind the expansion of the SfWRKY family. Additionally, several cis-acting elements related to stress response and hormone signaling were discovered within the promoter regions of SfWRKYs. Transcriptomic analyses across five tissues (leaves, flowers, pods, roots, and stems) revealed that genes exhibiting high expression levels in specific tissues generally showed high expression across all the examined tissues. Coexpression network constructed based on metabolomic and transcriptomic analyses of root and pod development indicated that SfWRKY29 may play significant role in regulating biosynthesis of secondary metabolites during the tissue development. The RT-qPCR results of gene expression analysis revealed that several SfWRKY genes were significantly induced in response to accumulation of secondary metabolites or salt stress. Our study systematically analyzed WRKY TFs in S. flavescens, which provides valuable reference data for further studies on key roles of SfWRKY genes in growth development as well as their responses under salt stress conditions.